Gregory and Leander : an analysis of the special friendship between Pope Gregory the Great and Leander, Archbishop of Seville - Martyn, John R. C. (Newcastle upon Tyne, UK : Cambridge Scholars, 2013)
"The book aims to reveal the hitherto totally unexamined relationship between these two most admirable and most courageous men, two really close friends who played major parts in establishing the orthodox Catholic faith in Europe near the end of the sixth century"--Page viii.
Includes bibliographical references (pages 127-135).
Description based on print version record.
Keywords: Gregory -- I, -- Pope, -- approximately 540-604.; Leander, -- Saint, Archbishop of Seville, -- -approximately 600.; Church history -- Primitive and early church, ca. 30-600.; RELIGION / Christianity / Catholic; Electronic books